Freeze food empire / Muhammad Fadhli Mohd Fuad ... [et al.] - Mohd Fuad, Muhammad Fadhli; Yusof, Muhammad Rasyidin; Mohd Isa, Muhammad Amirul Yusuf; Muhamad Hanif, Nur Nashriq Nu’aim (2021)
As we know, business opportunity is the important things people should grab to start a new business to generate our own income as a manager business or owner of the business. Business opportunity is the main reason for someone to create our own business as a well- known business in the future. Business opportunities should be taken by people who are interested in business and have knowledge in business management before starting their own business. Before start a own business, we should have a business plan that include all about entrepreneur knowledge, submit all ideas in starting a business and I will explain in this report.